Integrasi Pendidikan dan Penginjilan dalam Pembentukan Karakter - Dapot Damanik; Juspen Siringo-ringo; Ketler Sitohang; Ova Eniwati Habayahan (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
The formation of student character is very relevant in discussing the role of evangelism in shaping student character with integrity and faith. Thus, Christian religious education does not only focus on the delivery of theological dogma, but also on practical life with fellow human beings as seen from the character of students which can be done through education and evangelism in the school environment. As a Christian religious education teacher, it is expected to be able to organize the learning process and evangelism in the right way. This is where the need for the competence of a Christian religious education teacher in order to realize his duties professionally and responsibly. In completing this scientific paper, the author uses the method of literature study or library research with a descriptive qualitative approach.